Рroblems of PCR diagnostics OF COVID-19 - T. D. Grigorieva; M. А. Belopolskaya (Журнал инфектологии)
To date, an adequate and timely assessment of the number of cases is the basis of effective measures aimed at preventing the spread of COVID-19 infection. Real-time reverse transcription polymerase chain reaction (RT-PCR) remains the gold standard for confirming COVID-19.The purpose of the work: to analyze the experience of the city virological center of the S.P. Botkin Clinical Infectious Diseases Hospital (Botkin Hospital) for the examination for the presence of SARS-CoV-2 coronavirus by PCR in the period from 2020 to 2022.Materials and methods. The systematization of PCR studies on COVID-19 for the period 2020-2022 was carried out. A total of 221,901 people were examined, positive results were obtained in 55,372 (24.95%). Among the contingents of the examined patients, patients who underwent inpatient treatment at the Botkin Hospital.Conclusions. This study analyzed the possible causes of false-positive and false-negative PCR results. The correlation of the number of positive results with the dynamics of detection of new cases of COVID-19 in St. Petersburg during the 2020-2022 pandemic is shown. It has been established that the proportion of patients examined more than 3 times during the period of hospitalization remains significant. This fact requires the closest attention, given the high cost and laboriousness of PCR studies.